Vesicular uptake and exocytosis of L‐aspartate is independent of sialin. Issue 3 (6th December 2012) - Morland, Cecilie; Nordengen, Kaja; Larsson, Max; Prolo, Laura M.; Farzampour, Zoya; Reimer, Richard J.; Gundersen, Vidar
Abstract : The mechanism of release and the role of l ‐aspartate as a central neurotransmitter are controversial. A vesicular release mechanism for l ‐aspartate has been difficult to prove, as no vesicular l ‐aspartate transporter was identified until it was found that sialin could transport l ‐aspartate and l ‐glutamate when reconstituted into liposomes. We sought to clarify the release mechanism of l ‐aspartate and the role of sialin in this process by combining l ‐aspartate uptake studies in isolated synaptic vesicles with immunocyotchemical investigations of hippocampal slices. We found that radiolabeled l ‐aspartate was taken up into synaptic vesicles. The vesicular l ‐aspartate uptake, relative to the l ‐glutamate uptake, was twice as high in the hippocampus as in the whole brain, the striatum, and the entorhinal and frontal cortices and was not inhibited by l ‐glutamate. We further show that sialin is not essential for exocytosis of l ‐aspartate, as there was no difference in ATP‐dependent l ‐aspartate uptake in synaptic vesicles from sialin‐knockout and wild‐type mice. In addition, expression of sialin in PC12 cells did not result in significant vesicle uptake of l ‐aspartate, and depolarization‐induced depletion of l ‐aspartate from hippocampal nerve terminals was similar in hippocampal slices from sialin‐knockout and wild‐type mice. Further, there was no evidence for nonvesicular release of l ‐aspartate via volume‐regulated anion channels or plasma membrane excitatory amino acid transporters. This suggests that l ‐aspartate is exocytotically released from nerve terminals after vesicular accumulation by a transporter other than sialin.—Morland, C., Nordengen, K., Larsson, M., Prolo, L. M., Farzampour, Z., Reimer, R. J., Gundersen, V. Vesicular uptake and exocytosis of L‐aspartate is independent of sialin. FASEB J. 27, 1264–1274 (2013). www.fasebj.org